Perceptions and Reality: Revealing the BIM Gap Between the UK and Turkey - Ezcan, Volkan; Goulding, Jack Steven; Kuruoglu, Murat; Rahimian, Farzad Pour (IGI Global, 2013)
The complex nature of the construction process needs an intensive control and management mechanism in order to manage and process information flow. Current deficiencies in managing construction related information have been highlighted by a range of industry reports, the consensus of which has reinforced the lack of performance in the construction industry. Given this, recent research on the role of Building Information Modelling (BIM) has been proffered as a potential solution for covering these deficiencies, along with improving competitive advantage. Although limited research has concentrated on measuring BIM awareness and use, findings have been somewhat parochial and non-specific. This paper addresses this gap by concentrating on two markets: Turkey and the UK. The aim of the paper is to determine the BIM gap in terms of awareness and use, in order to form a basis for the development of future adoption strategies. A web-based questionnaire was used mirror the National Building Specification (NBS) survey (previously undertaken) in order to capture data from a new context (Turkey). The descriptive analyses of the findings and a comparison of the two countries are presented. The findings identify significant differences in BIM awareness the influence of which could provide insight for both mature and emerging markets.